Modelling of the Electrotonic Potential Distribution in Two-Dimensional Anisotropic Ohmic Me-dia - Grigaliunas, A.; Veteikis, R. (Elektronika ir Elektrotechnika, 1998)
As the myocardium is a complex three-dimensional anisotropic syncytial tissue, the parameters of myocardium as an electric medium cannot be measured directly. The experimental values of space constants of electrotonic decay lxe and lye are estimated and, by using mathematical models, their actual values lx and ly are found from which the values of the myocardial electric parameters are derived. During the experimental measurement, the current is delivered to the intracellular tissue through a circle-shaped suction-electrode. The present study includes theoretical simulation of the dependence of the values of space constants lxe and lye upon the size of the current source, the degree of electrotonic anisotropy and the distance between the current source and the measurement site of electrotonic potential. Evaluation of the correlation between the measured and actual electrotonic anisotropy is presented.